Impact of economic sanctions in the 1990s. - VAN BERGEIJK, Peter A.G. (1995)
Identifies six factors which explain why sanctions are and will be increasingly used: the end of the Cold War; strategic trade policy considerations; the greening of trade issues; proliferation of weapons of mass destruction and the related technology; scale economies in the implementation of sanctions; and the process of globalisation. Analyses the direct and hidden costs of intensified use of the economic sanction instrument.